An Evaluation of Paleomagnetic Techniques to Determine Emplacement Temperatures of Pyroclastic Density Currents at Mount St. Helens - (:unkn) unknown (My University, 2016)
During a volcanic eruption, pyroclastic density currents (PDCs) deposit new pumice and ash and rip out and transport lithic fragments from past eruptions. Magnetic minerals in the lithic fragments, such as titanomagnetite, may be partially or completely remagnetized, depending on their emplacement temperature with respect to their Curie and blocking temperatures. By finding the temperature at which this remagnetized overprint is removed, the emplacement temperature of the pyroclastic flow is estimated. This method assumes that the rock magnetic properties that govern magnetic unblocking are constant given a specific magnetic mineral composition, but recent studies demonstrate that Curie temperatures (Tc) in many natural titanomagnetites are a strong function of thermal history. Such variations in Curie temperature may bias estimates of PDC emplacement temperature. The purpose of this study is to evaluate the extent to which this is true. In 2014, ash, pumice, and lithic clasts from pyroclastic debris containing titanomagnetite were collected from the pumice fields north of Mount St. Helens in order to satisfy the three goals of this study. The goals of this study were to (1) examine how the temperature at which magnetization is removed varies with thermal history; (2) determine to what extent this might bias emplacement temperature estimates; and (3) to examine how stratigraphic variations in magnetic properties might be used to estimate emplacement temperature. In reference to goal #1, it has already been found that Curie temperatures in at least one section of the May 18th, 1980 flow increase with depth, in accordance with variations in cooling rates (Bowles et al., 2013). Unoriented pumice samples from the same section were thermally demagnetized, and it was found that blocking temperatures also increase with depth. The maximum unblocking temperature increased from ~415°C at the surface to ~465°C at 90 cm depth, suggesting that paleomagnetically-determined emplacement temperatures may be biased by up to ~50°C. This increase in unblocking temperature with depth is most plausibly explained by cation reordering. Cation reordering is a process in which the cations in the mineral titanomagnetite are allowed to move into a preferred alignment during slow cooling, which can increase the Curie temperature and, therefore, the emplacement temperature estimate. For goal #2, emplacement temperature estimates were made from lithic and pumice samples from sites 2, 4, 5, and 6 and were compared to measured emplacement temperatures of pyroclastic debris from the May 18, 1980 eruption (Banks and Hoblitt, 1996). The lithic samples were proven to provide more accurate results than the pumice, and the most robust deposit temperature estimate exceeded the measured emplacement temperature by ~40°C. Results overall demonstrate that overestimations of emplacement temperature estimates in samples with titanomagnetite do occur. To satisfy goal #3, analysis of the Curie temperature vs. depth from several locations allowed for qualitative assessments of emplacement temperatures. Because this can be conducted on ash matrix, it provides a means of crudely estimating temperature when no lithics are present. An elevated Tc1 (dominant Tc) or Tc that increases with depth is consistent with emplacement at temperatures above ~300⁰C, which is the minimum temperature at which cation reordering begins. This allows flows to be classified as emplaced at above 300⁰C or below 300⁰C, and the first four May 18th PDCs were found to oscillate about this temperature.